2014
DOI: 10.1177/1934578x1400900703
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant and Phagostimulant Activity of Extracts and Pure Compounds from Hymenoxys robusta on Spodoptera exigua (Lepidoptera: Noctuidae) Larvae

Abstract: In this study, the insecticidal and antifeedant activities of compounds from the leaves of Hymenoxys robusta on Spodoptera exigua, also known as armyworm, are reported. The methanol extract possessed suppressive activity, as well as a high antifeedant activity, suggesting that this extract has toxic effects on larvae. Compounds isolated from the plant show that a derivative of inositol and hymenolides stimulate the feeding, while vermeerin shows a high antifeedant effect. In addition, the methanol extract inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…amygdalina if their extraction can be optimised. [ 39 ] Vernonioside is one of several steroidal saponins known from V . amygdalina which causes the leaves to taste bitter[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…amygdalina if their extraction can be optimised. [ 39 ] Vernonioside is one of several steroidal saponins known from V . amygdalina which causes the leaves to taste bitter[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the contact toxicity in our research, we found that the LD 50 for larvae treated with isolated extracts were lower than LD 50 of crude extract. There are several studies indicating that phytochemicals from O. canum (Lamiaceae), O. sanctum (Lamiaceae), Rhinacanthus nasutus (Acanthaceae), Abrus precatorius (Fabaceae), Murraya koenigii (Rutaceae), Curculigo orchioides (Hypoxidaceae), Evolulus alsinoides (Convolvulaceae), Phyllanthus debilis (Phyllanthaceae), Swertia corymbosa (Gentianaceae), Zanthoxylum limonella (Rutaceae), Acorus calamus (Acoraceae), Piper retrofractum (Piperaceae), Hymenoxys robusta (Asteraceae) and Alpinia galanga (Zingiberaceae) had bioefficacy in protecting agricultural products from other Spodoptera species 20–22,58,59 …”
Section: Discussionmentioning
confidence: 99%
“…There are several studies indicating that phytochemicals from O. canum (Lamiaceae), O. sanctum (Lamiaceae), Rhinacanthus nasutus (Acanthaceae), Abrus precatorius (Fabaceae), Murraya koenigii (Rutaceae), Curculigo orchioides (Hypoxidaceae), Evolulus alsinoides (Convolvulaceae), Phyllanthus debilis (Phyllanthaceae), Swertia corymbosa (Gentianaceae), Zanthoxylum limonella (Rutaceae), Acorus calamus (Acoraceae), Piper retrofractum (Piperaceae), Hymenoxys robusta (Asteraceae) and Alpinia galanga (Zingiberaceae) had bioefficacy in protecting agricultural products from other Spodoptera species. [20][21][22]58,59 The effective LD 50 value of camphor, an isolated extract, caused a higher mortality than the crude extract. Similarly, many studies reported that the pure extract, ⊍-thujone from Hyptis marrubioides Epling, linalool and 1,8-cineole from Ocimum basilicum L. had more toxic effects on S. frugiperda larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The insecticidal and antifeedant activities of compounds and extracts from the leaves of Hymenoxys robusta on S. exigua were evaluated by Juárez et al (2014). The methanol extract possessed suppressive activity, high antifeedant activity and inhibited oviposition.…”
Section: Sesquiterpene Lactonesmentioning
confidence: 99%